Dos de cada tres enfermedades infecciosas descubiertas anualmente provienen de animales - ROMERO-ZUÑIGA, JUAN JOSÉ (2023)
https://open.spotify.com/episode/4Yy1EfhRGxaqFL2QnAYbvA?si=7jxR6R-CTneZoWfYrtacmw